2015
DOI: 10.1039/c4nr07224c
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite heterojunctions as sunlight-driven photocatalysts for hydrogen production from water splitting

Abstract: Hydrogen production via photocatalytic water splitting using sunlight has enormous potential in solving the worldwide energy and environmental crisis. The key challenge in this process is to develop efficient photocatalysts which must satisfy several criteria such as high chemical and photochemical stability, effective charge separation and strong sunlight absorption. The combination of different semiconductors to create composite materials offers a promising way to achieve efficient photocatalysts because doi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
267
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 451 publications
(271 citation statements)
references
References 227 publications
(239 reference statements)
2
267
0
2
Order By: Relevance
“…In this respect, some of the most relevant results collected in the literature review are reported in Table 2. At present, the most effective photocatalysts for photoreforming under visible light irradiation are CdS-based materials [125]. …”
Section: Methodsmentioning
confidence: 99%
“…In this respect, some of the most relevant results collected in the literature review are reported in Table 2. At present, the most effective photocatalysts for photoreforming under visible light irradiation are CdS-based materials [125]. …”
Section: Methodsmentioning
confidence: 99%
“…[44,45] Most literature reports for the synthesis of heterojunctions describe products in the shape of core-shells, thin films, microscopic beads grafted with nano-particles, or related. [4, 12,46] Heterojunctions are beneficial for water cleaning as there is a need to maximise charge separation in order to ensure the longest carrier lifetime. This will then favour the delivery of both the electrons and the holes to the catalyst surface where they will perform the target redox degradation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[8, 12] Many synthesis pathways are feasible but the sol-gel combined with an annealing step has been utilised initially to show bi-phasic materials of TiO 2 . A simple dip-coating procedure has led to controlled thickness layers of different phases of titanium dioxide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[Miranda et al 2014] Moreover, a very common explanation is the possible charge transfer process, considering the hybrid as semiconductor/metal junctions between planar electrodes. Reza Gholipour et al 2015] In this 2.1 Nanocarbon-based hybrids context, it is of interest to distinguish between hybrid and composites and also, give evidences of hybridisation that can probe the charge transfer process. The main distinction between both is the interfacial contact formed between components.…”
Section: Inorganic/nanocarbon Hybridsmentioning
confidence: 99%